Mapping the end times American evangelical geopolitics and apocalyptic visions - Dittmer, Jason; Sturm, Tristan (Farnham, Surrey, England ; Burlington, Vt. : Ashgate, 2010)
Over the last quarter-century, evangelicalism has become an important social and political force in modern America. Here, new voices in the field are brought together with leading scholars such as William E. Connolly, Michael Barkun, Simon Dalby, and Paul Boyer to produce a timely examination of the spatial dimensions of the movement, offering useful and compelling insights on the intersection between politics and religion. This comprehensive study discusses evangelicalism in its different forms, from the moderates to the would-be theocrats who, in anticipation of the Rapture, seek to impose their interpretations of the Bible upon American foreign policy. The result is a unique appraisal of the movement and its geopolitical visions, and the wider impact of these on America and the world at large.
Pt. 1. Contesting the American holy land. "What would Lee do? : religion and the moral landscapes of Southern nationalism in the United States / David Jansson -- Contests over Latter-Day space : Mormonism's role within evangelical geopolitics as seen through last-days novels / Ethan Yorgason -- Obama, son of perdition? : narrative rationality and the role of the 44th President of the United States in the end-of-days / Jason Dittmer -- pt. 2. American evangelical exceptionalism. Apocalyptic exceptionalism : Rosenberg, Clancy and the prophecy of Americanism / Simon Dalby -- The 'new world order' and American exceptionalism / Michael Barkun -- Imagining apocalyptic geopolitics : American evangelical Citationality of evil others / Tristan Sturm -- pt. 3. Missionary geopolitics. The problematic synergy between evangelicals and the US Senate in Sub-Saharan Africa / Hannes Gerhardt -- Reaching the unreached in the 10/40 window : the missionary geoscience of race, difference, and distance / Ju Hui Judy Han -- Between Armaggeddon and hope : dispensational premillennialism and evangelical missions in the Middle East / Carolyn Gallaher.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Evangelicalism -- United States; Christianity and international relations; Christianity and politics -- United States; Eschatology -- Political aspects -- United States; End of the world; Evangelikale Bewegung; Auserwählung; Endzeiterwartung; Apokalyptik; Geopolitik; USA; RELIGION / Christianity / History; Aufsatzsammlung; Electronic books